Fictitious Freedom: A Polanyian Critique of the Republican Revival. Issue 4 (4th July 2017) - Klein, Steven
Abstract: Prominent republican theorists invoke anonymous orders such as the market as mechanisms that secure freedom as non‐domination. Drawing on Karl Polanyi's account of fictitious commodities and demonstration of the impossibility of a just and rational market society, this article critically scrutinizes neo‐republican assumptions regarding the market, develops an alternate social theory within which to situate the ideal of non‐domination, and illustrates the importance of this reconfiguration for the kind of collective agents and political strategies that can be expected to advance republican freedom in the economy.